Role of microRNAs in host defense against porcine reproductive and respiratory syndrome virus infection: a hidden front line - Huang, Xuewei; Liu, Weiye (Frontiers in Immunology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most globally devastating viruses threatening the swine industry worldwide. Substantial advancements have been achieved in recent years towards comprehending the pathogenesis of PRRSV infection and the host response, involving both innate and adaptive immune responses. Not only a multitude of host proteins actively participate in intricate interactions with viral proteins, but microRNAs (miRNAs) also play a pivotal role in the host response to PRRSV infection. If a PRRSV–host interaction at the protein level is conceptualized as the front line of the battle between pathogens and host cells, then their fight at the RNA level resembles the hidden front line. miRNAs are endogenous small non-coding RNAs of approximately 20–25 nucleotides (nt) that primarily regulate the degradation or translation inhibition of target genes by binding to the 3-untranslated regions (UTRs). Insights into the roles played by viral proteins and miRNAs in the host response can enhance our comprehensive understanding of the pathogenesis of PRRSV infection. The intricate interplay between viral proteins and cellular targets during PRRSV infection has been extensively explored. This review predominantly centers on the contemporary understanding of the host response to PRRSV infection at the RNA level, in particular, focusing on the twenty-six miRNAs that affect viral replication and the innate immune response.